(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Road cracks may form as a result of climatic changes and low-quality building materials, which is important for maintenance as well as the fact that continual exposure would seriously harm the environment. The automated identification and classification of fractures in the surface of a road’s paving, without the need for manually labelled samples. This idea seeks to reduce human subjectivity that results from conventional visual surveys. The fracture identification process is initially carried out using learning from example photos extracted from the dataset. Non-overlapping picture blocks are categorised by the algorithm as either having crack pixels or not. The road photos can be used to find fractures in the pavement. With the aid of feature extraction from the photos, a supervised model is created for the detection of fractures in road photographs. The features were extracted, normalised, and then classified as either crack or non-crack based on the feature values produced. The picture is classified as cracked or not cracked based on the characteristics that were retrieved. During the testing phase, the pictures’ characteristics were retrieved and image fractures were located. By comparing the retrieved feature values with the suggested threshold, the fractures were then further divided into several categories. Finally, the process’ performance is assessed.